Direito de danos e reparação civil ambiental: o fundamento de teoria de direito privado da responsabilidade civil ambiental brasileira - LIMA, Gabriel Santos (Universidade Federal do Pará, 2023)
This research deals with civil liability for damage to the environment, evaluating a possible theoretical realignment of private law in the application of civil reparation. The work is divided into three parts. The first part initially presents the corrective and distributive models of civil liability, in order to understand the state of the art of the discussion on the right to damages. In the second stage, a doctrinal analysis is made of the elements of Brazilian objective civil liability, as well as the possible challenge presented by the application of the institute in the case of environmental damage. In the third and last part, the concepts of vulnerability are analyzed, in line with the conception of a new private law defended by Cláudia Lima Marques and Bruno Miragem, of distributive justice, based on the theory of Diego M. Papayannis, as well as possible repercussions from civil liability to the collective guardianship regime, based on idea of collective process. It appears that such concepts can be decisive for attributing civil liability for damage to the environment. Still in this last section, the case of programmed obsolescence of products is used to test the hypothesis. It is concluded that civil liability for damage to the environment can take advantage of vulnerability and distributive justice to promote a real change in the logic of private law.